The Effect of Learning Management by Using Context-Based on Mathematical Connection Ability and Attitude Toward Mathematics of Prathomsuksa 6 Students - Eaimlaor, Kotchakorn; Insombat, Bantita (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2024)
This research was a pre-experimental research. This research aimed to: 1) compare the mathematical connection ability of prathomsuksa 6 students before and after learning by using context–based learning, 2) compare the mathematical connection ability of prathomsuksa 6 students after learning by using context-based learning with the criterion of 70 percent of the full marks and 3) compare prathomsuksa 6 students’ attitude towards before and after learning by using context–based learning. The sample group consisted of 22 Prathomsuksa 6 students at Watlamwa School that selected by cluster random sampling. The research instruments were 1) 12 context-based learning plans, 2) the mathematical connections ability test and 3) the mathematic attitude test. The data was analyzed using the mean, standard deviation, dependent sample t-test and one-sample t-test. The research results found that: 1. The Prathomsuksa 6 students after learning by using context-based learning post-test was higher than pre-test with statistically significance at the .05 level. 2. The Prathomsuksa 6 students after learning by using context-based learning which was higher than the criterion of 70 percent of full marks with statistically significance at the .05 level. 3. The Prathomsuksa 6 students after learning by using context-based to attitude in Mathematics post-test was higher than pre-test with statistically significance at the .05 level.